2017
DOI: 10.1002/cjce.22901
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and desorption of carbon dioxide in several water types

Abstract: This study investigated the effect of water type on the rate of CO 2 transfer from/to an aqueous phase with varying degree of water salinity. The absorption and desorption experiments were conducted on reverse osmosis product, brackish well, and brackish water reverse osmosis reject waters as well as seawater in a mechanically agitated tank. Results show that the direction of mass transfer has a major impact on the value of the volumetric mass transfer coefficient, k L a, with the absorption experiments always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
(101 reference statements)
2
18
0
Order By: Relevance
“…For example, according to Millero, and for RO water, K 1 can be expressed as where T is the temperature in K and S is the salinity in g·kg –1 . Other relationships that apply for various types of water with varying degrees of salinity and alkalinity can be found, as summarized in Al-Hindi and Azizi …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, according to Millero, and for RO water, K 1 can be expressed as where T is the temperature in K and S is the salinity in g·kg –1 . Other relationships that apply for various types of water with varying degrees of salinity and alkalinity can be found, as summarized in Al-Hindi and Azizi …”
Section: Methodsmentioning
confidence: 99%
“…To perform these absorption operations, a wide array of gas–liquid contactors are typically employed. These contactors vary between mechanically agitated vessels, bubble columns, packed bed, and hollow fiber membranes. …”
Section: Introductionmentioning
confidence: 99%
“…Since the processes are open to the atmosphere, it is possible that dissolution of atmospheric CO 2 could cause some of the calcium to precipitate as CaCO 3 ; however, this effect was likely small because CO 2 was not actively injected into the solution, leading to a low gasliquid interfacial area, and thus a slow rate of CO 2 uptake. 45 The pH 4.8 and pH 7.0 products were recovered separately because they were expected to have considerably different P 2 O 5 grades and calcium to phosphorus (Ca/P) ratios; however, the results of these trials indicated that the properties of these two products are relatively similar; thus, it does not justify the use of two separation steps. Similarly, the two impurity products were Fig.…”
Section: Rsc Advances Papermentioning
confidence: 99%
“…It was noted that after each flow rate of water, appearance of column was changed ( Figure 4). Absorption analysis equipment is used to determine the rate of absorption of carbon dioxide into water [7] (Tables 1 and 2). It consist of two globes on the left side of the panel which are used to fill the caustic soda (NaOH) having sight tube on the right side to see the level which should retain at the level of '0' approximately such that extra unwanted caustic soda can be drain off through drain tube by using flask.…”
Section: Hydrodynamic Testmentioning
confidence: 99%